2023
DOI: 10.1001/jamaneurol.2023.2407
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Treatment Approaches for Super-Refractory Status Epilepticus

Abstract: ImportanceSuper-refractory status epilepticus (SRSE) is defined as status epilepticus (SE) that continues or recurs 24 hours or more after the onset of anesthetic therapy or recurs on the reduction/withdrawal of anesthesia. Current clinical knowledge of the disease and optimal treatment approach is sparse.ObjectiveTo systematically assess clinical characteristics, causes, outcomes, prognostic factors, and treatment approaches for patients with SRSE.Design, Setting, and ParticipantsIn this systematic review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 68 publications
1
8
1
Order By: Relevance
“…In this study, 50 SRSE patients received phenobarbital of whom only one patient failed treatment. The result was slightly different from the current meta-analysis 15 which revealed that phenobarbital revealed a nonsignificant trend toward worse outcomes at discharge. Based on this study, we suggested that phenobarbital might benefit the patients by the high prevalence of seizure control.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, 50 SRSE patients received phenobarbital of whom only one patient failed treatment. The result was slightly different from the current meta-analysis 15 which revealed that phenobarbital revealed a nonsignificant trend toward worse outcomes at discharge. Based on this study, we suggested that phenobarbital might benefit the patients by the high prevalence of seizure control.…”
Section: Discussioncontrasting
confidence: 99%
“…The whole mortality rate was similar to that reported previously. In the recently published meta-analysis, 15 the in-hospital mortality in SRSE patients was 24.1%. In this study, the mortality of in-hospital mortality and 6 months after discharge in the SRSE group were 11.8% and 31.4%, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Of note, in our study, SRSE was not significantly associated with an overall increased risk of RS, but when RS occurred, the risk of develop DRE was higher. From this point of view, it is worth noting that mortality is high in the case of SRSE and survivors are left with severe disabilities [44]. Therefore, patients with SRSE may have died prior to experience unprovoked seizures, but once it occurred, post-SE epilepsy was drug-resistance in the majority of cases (5/6 patients).…”
Section: Post-se Drementioning
confidence: 99%